Pengaruh Komitmen Profesional, Personal Cost, dan Gender Terhadap Intensi Whistleblowing - Novia; Nindito, Marsellisa; Zakaria, Adam (LPPM Universitas Negeri Jakarta, 2023)
This study aims to examine whether there is an influence of professional commitment, personal cost, and gender on whistlenlowing intention. The population in this study were auditors who worked at KAP in East Jakarta. The number of samples in this study were 41 respondents. The sampling technique uses purposive sampling method. The research method used is quantitative with primary data sources. The methode of data analysis uses multiple linear regression analysis with SPSS version 25. The results of this study prove empirically that personal cost have a positive significant effect on whistleblowing intention. Meanwhile professional commitment and gender have no effect on whistleblowing intention